A Bibliometric Study: The Historiography of the Jewish National Movement - Mustigman, Hava (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
The paper presents a bibliometric study which analyses the research literature published during sixty years on the Jewish National movement prior to the establishment of the State of Israel. The main research issues in the present study are the rate of growth of the related research literature from 1948 to 2005 by decades; main publication types and their segmentation; languages, countries of publication and the leading universities where the research was performed. The paper compares also the compatibility of the findings of the bibliometric study with the conclusions of historiographic and bibliometric literature, and the factors that influenced  the study of the topic during six decades.